LOCAL WISDOM-BASED LITERARY LITERACY IN LANGUAGE AND LITERATURE LEARNING FOR SENIOR HIGH SCHOOL STUDENTS IN TERNATE: STRATEGIES AND OBSTACLES - Samsudin Hi Adam; Anwar Ismail; Silvani Umar Ali (Universitas Islam Sumatera Utara (UISU), 2022)
Literary literacy needs to be cultivated to fight the impact of globalization which has made the local culture eroded and increasingly marginalized and has even begun to show symptoms of being forgotten. Thus, study on local wisdom-based literary literacy needs to be carried out to reveal the values contained in it through the literary literacy movement as reinforcement of language and literature learning. This study uses a qualitative method. The data sources are obtained from teachers, librarians, students, and related parties in school as well as learning plan documents arranged in the lesson plans and students’ learning outcomes. The data are collected through interviews, observation, and documentation. The results indicate that literacy activities in literary learning focus on reading, understanding, interpreting and responding to literary reading texts. The teachers integrate the values of local wisdom in all stages of literary learning carried out in three phases, namely initial activities, main activities and closing activities. This has positive impact on students not only in terms of academic but also non-academic.The obstacles encountered in its implementation are the low interest of students in reading, the lack of teachers’ understanding of North Maluku local wisdom, the lack of learning methods and varied learning media, and the lack of references to literary books containing local wisdom available in school library. The findings imply that literary literacy based on local wisdom applied by teachers in learning can develop students’ awareness of local cultures. However, it has not been able to improve the students’ literacy skills.